Bounds of Solutions of Integrodifferential Equations - Zdeněk Šmarda (Abstract and Applied Analysis)
Some new integral inequalities are given, and bounds of solutions of the following integro-differential equation are determined: x'(t)-F(t,x(t),∫0tk(t,s,x(t),x(s))ds)=h(t), x(0)=x0, where h:R+→R, k:R+2×R2→R, F:R+×R2→R are continuous functions, R+=[0,∞).